Kolaborasi Model PBL Dan Model STAD dalam Pembelajaran Ekonomi - Rizka Andriyati; Leny Noviani (Universitas Negeri Surabaya, 2023)
Economic learning had a complex subject matter and high relevance in daily life. The output of economic learning was that students had good critical thinking skills as demanded by 21st century skills. However, during this time economic learning seem too bored because the learning only based on the theory without connected to contextual activities. This research used literature study method with the purpose to reviewed the collaboration model of PBL and STAD theoretically in improving student’s critical thinking skills in economic learning. The implementation of collaboration model of PBL and STAD could be done in six steps there are class presentation, team formation and work in group, identified the problem that provided by teacher then students find information from any resources in solving problem, organizing quiz, scoring and team recognition.